Shariah-Driven Healthcare: Bridging Knowledge, Cost, and ‎Compliance - Fadzil, Mohd Khairul Ridhuan Mohd; Mat, Hamidah (RABBANICA - Journal of Revealed Knowledge, 2025)
This study aims to investigate the reasons behind healthcare practitioners’ limited knowledge of Shariah principles and analyse how high operational costs impact the proper functioning of Shariah-approved hospitals. Using qualitative methods, the study used semi-structured interviews and field observations with five purposively selected health care professionals, hospital management and clinical staff who were directly engaged in Shariah-compliant practices. The results unveil essential discrepancies resulting from the dearth of specialised training and the unavailability of systematic, actionable guidelines articulating the implementation of Shariah norms in clinical spaces. Moreover, sourcing halal-certified medical supplies has a financial burden, impacting operational efficiency. To address this issue, the study proposed an integrated approach with three interconnected pillars: designing and instituting systematic Shariah-mindset training programmes; the use of Shariah-compliant financial mechanisms such as zakat and waqf for strategic financial utilisation; and establishing standardised operational guidelines specifically to develop Shariah compliance in the healthcare management approach.